Implantace multifokální nitroocní cocky - Urminský, J; Rozsíval, P; Feuermannová, A; Lorencová, V; Jirásková, N (Ceska a slovenska oftalmologie, 2004)
The authors refer to the first experience in implantation of multifocal intraocular lens (MIOL) AMO ARRAY (model SA 40 N) produced by Allergan to a group of 35 patients (69 eyes). The proportion of men in the group was 42.9%, women being 57.1%. The mean age of the group was 50.9 +/- 4.3 year, range 36-71 years. The implantation of this type of intraocular lens was made due to a refractory intervention on a clear lens in 84.0% eyes and operation on cataract in 16.0%. The study was aimed at evaluation of the results of visual acuity for short and long distances, resulting refraction after the operation, the occurrence of side visual phenomena and their tolerance by the patient, necessary supplementary eyeglass correction especially in patients after refraction lensectomy. Uncorrected visual acuity for long distances 0.7 or better was in 75.9% of patients. Sixty one % of patients with MIOL in both eyes do not require glasses for vision into short distances (No 1-3).
Keywords: dospělí; Visual Acuity; Humans; Cataract Extraction; lidé středního věku; Middle Aged; oční čočka; zraková ostrost; mužské pohlaví; Lenses, Intraocular; refrakční chirurgické výkony; extrakce katarakty; nitrooční čočky; Adult; Lens Implantation, Intraocular; ženské pohlaví; Lens, Crystalline; lidé; Refractive Surgical Procedures; implantace nitrooční čočky; Aged; senioři; Male; Female